Health Diplomacy and Domestic Political Stability: A Qualitative Analysis of European Union Support for Public Health Programs in Indonesia - Dwi Untari Fadillah Asih; Sholihul Absor; Mundakir Mundakir; Pipit Festi Wiliyanarti; Muhamad Bayhaqi (Malahayati Nursing Journal, 2026)
ABSTRACT Health diplomacy has become a crucial element in global governance, serving not only to improve national health capacities but also as an instrument of soft power for donor countries. Within this framework, the European Union (EU) actively engages in international health initiatives, positioning itself as both a normative power and a key global health actor. Indonesia, as a strategic partner in Southeast Asia, provides a compelling case to examine how external health diplomacy influences domestic political dynamics. This study aims to analyze the role of the European Union (EU) in health diplomacy in Indonesia and to assess its implications for domestic political stability. The research seeks to understand how EU-led health cooperation contributes to strengthening Indonesia’s health system and the legitimacy of its government in the public domain. Using a qualitative research design with a case study approach, this study examines policy documents, official EU communications, Indonesian Ministry of Health reports, and WHO publications. The analysis focuses on identifying the forms of EU support, the key actors involved, the mechanisms of implementation, and the political effects arising from such collaborations. The findings reveal that the EU’s health diplomacy in Indonesia encompasses financial assistance, technical cooperation, joint research programs, and vaccine distribution. These initiatives collectively enhance Indonesia’s health system capacity while reinforcing public trust and governmental legitimacy. Furthermore, health diplomacy operates as a soft power tool for the EU, strengthening its normative and humanitarian image in the global order. This study concludes that the EU’s health diplomacy plays a dual role: it contributes to domestic stability in Indonesia through capacity building and simultaneously projects the EU’s identity as a normative global actor. The research highlights the need for transparent, adaptive, and sustainable international health collaborations. It also encourages comparative analysis with other global actors such as China, the United States, and ASEAN to better understand variations in health diplomacy strategies and their political outcomes. Keywords: Health Diplomacy, European Union, Indonesia, Soft Power, Political Stability, Global Health Governance.